Living Hadits Oral, Lisan, dan Tulisan Jamaah Maiyah, Emha Ainun Najib, dan Gamelan Kyai Kanjeng - Andi Winata As'ari (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2018)
This article aims to discuss the unique Living Hadis which exists on Gamelan Kiai Kanjeng and explains how hadis understood by Emha Ainun Najib as a speaker in every event they held. Thus, this research finds that some of the event held by Kiai Kanjeng and Emha Ainun Najib is an exspression of sunnah due to Emha always invites all audiences to be independence and teaches them how to face and manage problem in their life. Also, Emha and Kiai Kanjeng are able to give good interpretations to Holy Qur’an and Sunnah that agree with the conditions of Indonesians wihich have multicultured and multireligious nations. Throught metodological study, the author find that Kiai Kanjeng is one of organisations that practice and deliver sunnah for all classes and grades of society, such as: moslem or non moslem, college students, workers, public staff, teachers and many others. There are explanations of performance of Emha Ainun Najib that can be considred as living of sunnah, for instance: Having shalawatan together, problem solving, social respons, political education, and interpreations of normative text of Holy Qur’an and Hadis which is able to support and advise Indonesian people. Emha Ainun Najib is not only a pious speaker who practices living sunnah orally but also a character who can do living sunnah in writing. Gamelan Kiai Kanjeng with Emha Ainun Najib is a group of musical instrument which colaborated with some other music toos such as Guitar, Piano, band, and others. It can stimulate suciety to worship by listening and saying shalawat together in happy conditions and is going to produce good character of human being.